1998
DOI: 10.1002/(sici)1521-3765(19981002)4:10<2037::aid-chem2037>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Aza-aziridinofullerene: Interconversion between Aza-aziridinofullerene and Bisazafulleroid

Abstract: The synthesis and spectroscopic characterization of a novel bisazafulleroid (12) and aza-aziridinofulleroid (13) are described. Treatment of C 60 fullerene with the C 2 -chiral bisazide 11 in refluxing chlorobenzene afforded bisazafulleroid 12 in 20 % yield. When a solution of 12 was exposed to ambient light a quantitative conversion to the more polar 13, in which the two imino groups add at both [5,6] and [6,6]-ring junctions, was observed. The two compounds exhibited characteristic absorption profiles in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 5 publications
3
16
0
Order By: Relevance
“…In the course of our study on the development of synthetic methodology for the preparation of [1,2]aziridinofullerene,2 we carried out the photoreaction of C 60 with an N ‐ p ‐toluenesulfonylsulfilimine7 having a dibenzothiophene structure ( 3 ; Scheme ) to accomplish the regioselective synthesis of N ‐tosyl[1,2]aziridinofullerene ([6,6]‐closed C 60 NTs, 4 ). It is well known that 1,6‐azafulleroids 1 readily cyclize thermally and photochemically to afford [1,2]aziridinofullerenes 2 , while the reverse reaction hardly occurs 8. This finding may indicate that 2 is more thermally stable than 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the course of our study on the development of synthetic methodology for the preparation of [1,2]aziridinofullerene,2 we carried out the photoreaction of C 60 with an N ‐ p ‐toluenesulfonylsulfilimine7 having a dibenzothiophene structure ( 3 ; Scheme ) to accomplish the regioselective synthesis of N ‐tosyl[1,2]aziridinofullerene ([6,6]‐closed C 60 NTs, 4 ). It is well known that 1,6‐azafulleroids 1 readily cyclize thermally and photochemically to afford [1,2]aziridinofullerenes 2 , while the reverse reaction hardly occurs 8. This finding may indicate that 2 is more thermally stable than 1 .…”
Section: Methodsmentioning
confidence: 99%
“…By controlling the length and geometry of the tether, either equatorial , or cis-2 , or even trans-2 and trans-1 , structures could be almost exclusively obtained. Other attempts to tether-control bisadditions have given alternate fortunes. …”
Section: Introductionmentioning
confidence: 99%
“…10, [16][17][18][19] In these studies, the data on these structures were compared with related or ganic compounds, and it was concluded that only struc ture III contains no carbon atoms, whose signals would appear in the 13 C NMR spectra outside the region δ 133-146. Based on this conclusion, we have assigned 11 the structure of regioisomer III to compound 2.…”
Section: Methodsmentioning
confidence: 99%